China-Taiwan Relation During Tsai’s Presidency and Her Efforts in Maintaining Taiwan As Self-Governing Region - Ha, Hengyii; Lucy, Sebli Seidelson (Penerbit UKM (UKM Press), 2025)
Tensions between China and Taiwan have escalated, particularly during President Tsai’s tenure. Following World War II, China endured the Chinese Civil War between the Chinese Communist Party (CCP) and the Kuomintang (KMT). The KMT’s defeat in 1949 marked the end of the conflict, after which it retreated to Taiwan and became an opponent force to Beijing. Since then, Cross-Strait relations have remained tense. Under President Tsai, the issue has become more apparent as she consistently rejects China’s reunification agenda while strengthening Taiwan’s ties with Southeast Asian countries and the United States (U.S.) in particular. This paper also adopts a qualitative desktop research, relying on secondary data collection method which includes treaties, white papers, policy documents, defense reports, and news articles. This paper is also significance because Democratic Progressive Party (DPP) prioritizes safeguarding Taiwan’s autonomy and democratic values and the Kuomintang (KMT) advocates for closer ties with China. Concurrently, scholarly attention to the contemporary dynamics of Cross-Strait relations remains insufficient. Existing studies often focus on outdated analyses, such as the deficiencies in Taiwan’s 2012 elections, rather than the policies and developments under Tsai Ing-wen’s administration (2016–2024). Therefore, this paper examines ChinaTaiwan relationship during Tsai’s presidency demonstrates the significance of defending Taiwan’s democracy and maintaining its status quo as an autonomous territory within China